Implementation of Journalistic Language in The UMKM and Cooperatives Column in The Online Media ekorantt.com - Maria Triensy Oktaviana; Lodowik Nikodemus Kedoh; Viktor Ariestyan Sedu (IJESS International Journal of Education and Social Science, 2024)
Mass media plays an essential role in delivering information to a wide and diverse audience, including in economic reporting. Journalistic language, as a medium of mass communication, must adhere to the principles of clarity and simplicity to enhance readers' understanding. However, the implementation of journalistic language in online media is often suboptimal, with various issues such as ineffective sentences, improper spelling, and inefficient word usage. This study focuses on the application of journalistic language in reporting on MSMEs in the online media Ekorantt.com. This research employs a qualitative approach with observation, document study, and text analysis methods on three selected news articles. Data analysis follows the Miles and Huberman model, including data collection, data reduction, data presentation, and conclusion drawing. The results show that although the three articles have implemented most of Hemingway's principles, such as using short, active, and simple sentences, several deficiencies remain, such as repeated information, lengthy compound sentences, and irrelevant phrases. In conclusion, by simplifying sentences, enhancing language efficiency, and avoiding irrelevant elements, text quality can be improved to meet Hemingway's journalistic standards, producing clearer, more engaging, and efficient news articles.